P785 A retrospective cohort study on vedolizumab trough levels in Crohn's disease patients. (30th January 2023) - Pokryszka, J; Stadlmann, M; Primas, C; Gerold, N; Reinisch, S; Novacek, G; Reinisch, W
Abstract: Background: Background: Vedolizumab (VDZ), an α47-integrin inhibitor, is approved for the treatment of moderate to severe Crohn's disease (CD). Exposure-response relationship for VDZ is less evident in CD. Here, we are exploring associations between serum VDZ serum concentrations and clinical/biomarker-defined endpoints from a single center, real-world cohort. Methods: Methods: Electronic health data records of CD patients during their first year of treatment with VDZ from January 2014 – July 2022 at our tertiary care center were obtained. Serum drug levels (TDL) and their correlation with outcomes were assessed at specified timepoints – weeks 12 (± 2), 26 (± 4) and 52 (± 6). Clinical remission was assessed by patient reported outcomes as suggested in STRIDE II guidelines (stool frequency ≤ 3 and abdominal pain ≤ 1). Fecal calprotectin (fCP) values ≤ 150 µg/g marked biomarker remission. Vedolizumab drug levels were measured with IDKmonitor Vedolizumab drug level ELISA kit (Immundiagnostik AG, Germany), In case of missing data patients were categorized as non-responders. For association modelling, multivariable fractional polynomials and generalised additive models were used (R statistical software, v4.1.2; R Core Team). Results: Results: In total, 58 patients (females = 55.2%) with at least two available data points were included (Table 1). Sixteen individuals (16/58, 27.6%) were naive for biologics therapies. 98.3% (57/58) reached week 12 (± 2). Both at weeks 26 and 52 91.4% (53/58) subjects still were on drug. Clinical remission was achieved in 51.7% (30/58), 49.1% (26/53) and 45.2% (24/53) cases at weeks 12, 26 and 52, respectively, with biomarker remission rates of 24.1% (14/58), 35.8% (19/53) and 27.6% (16/53) patients reached biomarker remission. TDLs differed only between clinical remitters and non-remitters at week 26 (Mann-Whitney-U-test, p = 0.04). Also, there was no significant association between clinical and biomarker remission at defined timepoints and corresponding TDLs (for all p > 0.05). TDLs at week 2 and 6 were correlated with fCP values at the same time (rho: -0.327, p = 0.03 at week 2 and rho: -0.356, p = 0.02 at week 6). When TDLs at week 2 and week 6 were taken into consideration and associated separately with therapy outcomes in a univariate regression, only association between serum levels at week 6 and biomarker remission at weeks 26 and 52 was found ( p = 0.02 and p = 0.03, respectively). Conclusion: Conclusion: The only association between serum drug levels and remission was found between TDLs at week 6 and biomarker remission at weeks 26 and 52 suggesting a complex exposure-response relation for vedolizumab in CD patients.